(untitled) (Bangladesh Journal of Dental Research & Education, 2014)
The management of Oral submucous fibrosis has been the subject of controversy ever since Schwartz first described the condition in 1952. It is potentially malignant disorder and crippling condition of oral mucosa. An attempt is made update the knowledge about the management of this precancerous condition with advancements which helps to reduce the mortality of oral cancer. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20256 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 88-90